Who Uses Green Mobility? Exploring Profiles in Developed Countries - Lucía Echeverría; J. Ignacio Gimenez-Nadal; José Alberto Molina (Institute of Labor Economics (IZA), 2021)
Mobility gives individuals access to different daily activities, facilities, and places, but at the cost of imposing environmental burdens. The sustainable growth of society is linked to green mobility (e.g., public transport, walking, cycling) as a way to alleviate individual carbon footprints. This study explores the socio-demographic profile of individuals performing green travel (public and physical modes of transport) and identifies cross-country differences in green travelling behavior. We rely on information from the Multinational Time Use Study, MTUS. for Bulgaria, Canada, Spain, France, Hungary, Italy, the Netherlands, the United Kingdom, and the United States, from 2000 to 2019. We estimate Ordinary Least Squares regressions modelling individual decisions regarding green mobility. Our results indicate that the socio-demographic and family profile of travelers is not homogenous across green modes of transport, with physical travel exhibiting a much more consistent profile, across countries, in comparison to the use of public transport. Results indicate a positive relationship between living in urban areas and the time proportion of green travel, but estimates by country differ in magnitude and depend on the mode. We also find that some countries are more prone to green travel, and that transport infrastructure is more related to the proportion of time travelled by physical transport than by public transport. Our findings help in understanding who is committed to green mobility, while revealing systematic differences across countries that are worth analyzing.
Keywords: R40; J22; O57; 330; green mobility; public transport; walking/cycling; Multinational Time Use Study